Ménière's Disease: A CHEER Database Study of Local and Regional Patient Encounter and Procedure Patterns. (1st July 2016) - Crowson, Matthew G.; Schulz, Kristine; Parham, Kourosh; Vambutas, Andrea; Witsell, David; Lee, Walter T.; Shin, Jennifer J.; Pynnonen, Melissa A.; Nguyen‐Huynh, Anh; Ryan, Sheila E.; Langman, Alan
Abstract : Objective: (1) Integrate practice‐based patient encounters using the Dartmouth Atlas Medicare database to understand practice treatments for Ménière's disease (MD). (2) Describe differences in the practice patterns between academic and community providers for MD. Study Design: Practice‐based research database review. Setting: CHEER (Creating Healthcare Excellence through Education and Research) network academic and community providers. Subjects and Methods: MD patient data were identified with ICD‐9 and CPT codes. Demographics, unique visits, and procedures per patient were tabulated. The Dartmouth Atlas of Health Care was used to reference regional health care utilization. Statistical analysis included 1‐way analyses of variance, bivariate linear regression, and Student's t tests, with significance set at P <. 05. Results: A total of 2071 unique patients with MD were identified from 8 academic and 10 community otolaryngology–head and neck surgery provider centers nationally. Average age was 56.5 years; 63.9% were female; and 91.4% self‐reported white ethnicity. There was an average of 3.2 visits per patient. Western providers had the highest average visits per patient. Midwest providers had the highest average procedures per patient. Community providers had more visits per site and per patient than did academic providers. Academic providers had significantly more operative procedures per site ( P =. 0002) when compared with community providers. Health care service areas with higher total Medicare reimbursements per enrollee did not report significantly more operative procedures being performed. Conclusion: This is the first practice‐based clinical research database study to describe MD practice patterns. We demonstrate that academic otolaryngology–head and neck surgery providers perform significantly more operative procedures than do community providers for MD, and we validate these data with an independent Medicare spending database.